2021
DOI: 10.3390/microorganisms9122499
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Citric Acid and Cr Resistant Microbes Improved Castor Bean Growth and Photosynthesis while It Alleviated Cr Toxicity by Reducing Cr+6 to Cr3+

Abstract: Chromium is highly harmful to plants because of its detrimental effects on the availability of vital nutrients and secondary metabolites required for proper plant growth and development. A hydroponic experiment was carried out to analyze the effect of citric acid on castor bean plants under chromium stress. Furthermore, the role of two chromium-resistant microorganisms, Bacillus subtilis and Staphylococcus aureus, in reducing Cr toxicity was investigated. Different amounts of chromium (0 µM, 100 µM, 200 µM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 78 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Soil bacteria develop a continual contact with the pollutants present in the soil or in the polluted water used for irrigation [8,9]. Recently, Ali et al [10] indicated the bacterial species that can be used in the remediation of heavy metals from the rhizosphere. For the first time, they used a consortium of two different bacteria (i.e., Bacillus subtilis and Staphylococcus aureus) to reduce the chromium (Cr) from the rhizosphere of castor beans.…”
mentioning
confidence: 99%
“…Soil bacteria develop a continual contact with the pollutants present in the soil or in the polluted water used for irrigation [8,9]. Recently, Ali et al [10] indicated the bacterial species that can be used in the remediation of heavy metals from the rhizosphere. For the first time, they used a consortium of two different bacteria (i.e., Bacillus subtilis and Staphylococcus aureus) to reduce the chromium (Cr) from the rhizosphere of castor beans.…”
mentioning
confidence: 99%